Interest rates, money supply, institutional quality, and exchange rate stability in Nigeria - Ademola, Olufemi; Alalade, Yimka S A; Ogbebor, Peter; Lawal, Esther (The Economics and Finance Letters, 2024)
The purpose of this paper was to examine the intricate relationship between interest rate and exchange rate, exploring their interdependencies, mechanisms, and implications for policy management and economic stability in Nigeria, and to also shed light on the complex dynamics that govern these two fundamental pillars of financial markets, as well as the appropriateness of the continuous use of interest rates to manage the Nigeria’s currency exchange rate. This is because, since the mid-2000s, the Central Bank of Nigeria (CBN) has consistently used interest rate adjustment as a policy tool to manage exchange rate volatility, with mixed outcomes. The study utilised a dataset consisting of 68 quarters of time series data, spanning from 2006Q1 to 2022Q4, and adopted the Autoregressive Distributed Lag (ARDL) model to evaluate the influence of interest rates, money supply growth, and institutional quality on exchange rate stability in Nigeria, employing an ex-post facto research approach. Using the ARDL to test the hypothesis, the study found that monetary policy rate and money supply have long-run insignificant cointegrating relationships with exchange rate in Nigeria (Adj R2=0.642; F-stat (4, 63) = 53.813, p<0.05). The study concluded that interest rates have a significant impact on exchange rates in Nigeria. The study found that the independence of the CBN and adoption of capital mobility, and a fixed exchange rate mechanism in Nigeria are a violation of the principle of “impossible trinity” of fixed exchange rates and recommended a review of the exchange rates management policy.